Lactic Acid as Spacer between Poly Acrylic Acid and 4-Aminoantipyrine - Ali, Fiyral Mohammad; AL-Noor, Taghreed Hashim; Ali, Saif Mohsin (The International Journal of Biotechnology, 2015)
Due to many problems associated with drug release and side effects, we could design a novel drug delivery system through modification of poly acrylic acid (AA) with Lactic acid as a spacer between the polymer and 4-aminoantipyrine. In vitro drug release had been conducted successfully in basic medium in pH 7.4 and acidic medium in pH 1.1 at 37℃. The prepared prodrug polymer was characterized by FTIR and 1H−NMR spectra. Physical properties and intrinsic viscosity of drug polymer were determined. The good results were obtained in the presence of spacer unit with comparing without spacer unit.